Politik Uang Dalam Pemilu Ditinjau Dari Perspektif Yuridis Sosiologis - Retna Susanti (Lex Renaissance, 2021)
This study aims to analyze the formulation of money politics criminal acts in the Election Law and examine law enforcement on money politics from a sociological perspective. The choice of the sociological juridical approach method is intended to photograph the application and study of the relationship between legal aspects and non-legal aspects in the operation of law in society. Gaining votes in elections can be reached with non-monetary power, such as through family, social and economic networks, but the portion of the determination is more with money politics. The results of the study conclude that the formulation of money politics in the Election Law is not progressive enough so that it needs to be reformed. In addition, from a sociological perspective, the effectiveness of resolving election crimes related to money politics is largely determined by public awareness and participation.Key Words: Election criminal law; law enforcement; money politicsAbstrakPenelitian ini bertujuan untuk menganalisis perumusan tindak pidana politik uang dalam Undang-Undang Pemilu dan mengkaji penegakan hukum atas tindak pidana politik uang dari perspektif sosiologis. Pemilihan metode pendekatan hukum yuridis sosiologis dimaksudkan untuk memotret penerapan dan pengkajian hubungan aspek hukum dengan aspek non hukum dalam bekerjanya hukum di masyarakat. Pendulangan suara dalam pemilu dapat dijangkau dengan kekuatan non uang, seperti melalui jaringan keluarga, sosial dan ekonomi, tetapi porsi penentuan lebih banyak dengan politik uang. Hasil penelitian menyimpulkan bahwa perumusan tindak pidana politik uang dalam Undang-Undang Pemilu tidak cukup progresif sehingga perlu dilakukan pembaharuan. Selain itu, ditinjau dari perspektif sosiologis, efektivitas penyelesaian tindak pidana pemilu terkait politik uang, banyak ditentukan oleh kesadaran dan partisipasi masyarakat.Kata Kunci: Politik uang; hukum pidana pemilu; penegakan hukum